Pemberdayaan Usaha Mikro Abon Lele - Romindo Pasaribu; Audrey Siahaan (LPPM Universitas HKBP Nommensen, 2021)
The development of MSMEs in North Sumatra is quite good, namely around 2.8 million business units, and has contributed quite well to economic growth in North Sumatra and Medan in particular. MSMEs in the city of Medan are not seen as an alternative, but have become the backbone or foundation of the economy in Medan. There are 3 (three) things that must be considered and improved to strengthen the foundations of MSMEs, namely, finance, increase in human resources, and innovation in marketing models. The Yoppie Belawan Community is one of the home industries in Medan Belawan District. Precisely on Jalan Selebes Belawan II, Medan Kota Belawan, North Sumatra 20411. Since the beginning of 2020, the Yoppie Belawan Community started a catfish farming business. In April 2020, this community decided to process catfish meat into something more valuable and able to help this community increase their income and welfare during the current pandemic. After going through various considerations, it was decided to process catfish meat into Shredded Catfish with the IndoFish Shredded Catfish brand.